Optical measurements on tailored zinc oxide thin films under optimal - R. Haarindraprasad; U. Hashim; Subash C.B. Gopinath; P. Veeradasan; Wei-Wen Liu; B. Sharma Rao; V. Thivina (Elsevier, 2024)
Non-Indexed Publication